2017
DOI: 10.1371/journal.pone.0172360
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial comparisons of the reproductive biology of northern Gulf of Mexico (USA) red snapper (Lutjanus campechanus) collected a decade apart

Abstract: In studies done a decade apart, we provide evidence of a recent shift toward a slower progression to sexual maturity as well as reduced egg production, especially among young, small female red snapper, in the Gulf of Mexico (Gulf). Slower maturation rates (among fish ≤6 years old), lower GSI values and decreased spawning frequency were observed, and were especially pronounced in the northwestern Gulf. Furthermore, an Index of Reproductive Importance showed that young fish (ages 2–7) are contributing far less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…; Kulaw et al. ). Additionally, some differences in reproduction, including GSI, SFE, and batch fecundity (BFE), were found among six geographical regions spanning the northern Gulf from central Florida to south Texas (Kulaw ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…; Kulaw et al. ). Additionally, some differences in reproduction, including GSI, SFE, and batch fecundity (BFE), were found among six geographical regions spanning the northern Gulf from central Florida to south Texas (Kulaw ).…”
mentioning
confidence: 97%
“…Previous studies of Red Snapper reproduction in the Gulf have been focused offshore of Alabama and Louisiana (Collins et al 2001;Woods et al 2003;Jackson et al 2006Jackson et al , 2007Kulaw 2012;Glenn et al 2017), Florida (Brown-Peterson et al 2008, and the Yucatán Peninsula (Brulé et al 2010). Off Louisiana, differences in gonadosomatic index (GSI), maturity, and spawning frequency (SFE) were found among natural shelf-edge banks, standing platform sites, and toppled platform sites; however, due to geographical constraints, these habitats were located across a wide depth range (i.e., 55-160 m;Kulaw 2012;Glenn et al 2017;Kulaw et al 2017). Additionally, some differences in reproduction, including GSI, SFE, and batch fecundity (BFE), were found among six geographical regions spanning the northern Gulf from central Florida to south Texas (Kulaw 2012).…”
mentioning
confidence: 99%
“…Based on the ages of Red Snapper collected in this study and the reported age at 50% maturity of 4.5 years for Red Snapper in the western GOM (Gallaway et al 2009;Kulaw et al 2017), a vast majority of individuals inhabiting CCNR were juveniles. An ontogenetic habitat shift has been suggested for Red Snapper, and juveniles can move from lowrelief shell rubble habitats to intermediate-relief structures within the first year (Wells et al 2008c;Gallaway et al 2009).…”
mentioning
confidence: 88%
“…Red Snapper become reproductively mature between 2 and 8 years of age, with apparent individual variation through time and across regions (Kulaw et al. ). During this period, Red Snapper continue to occupy high‐relief habitat, spanning the width of the continental shelf, with larger individuals shifting to reefs with increasing vertical height and complexity.…”
Section: Red Snapper Life‐cycle and The Need To Scale Catch To Commonmentioning
confidence: 99%
“…Given that this ontogenetic shift appears to be related to the increasing body size of Red Snapper precluding them from sheltering in shell rubble, the snapper that do not recruit to highrelief habitats are likely subject to predation. Red Snapper become reproductively mature between 2 and 8 years of age, with apparent individual variation through time and across regions (Kulaw et al 2017). During this period, Red Snapper continue to occupy high-relief habitat, spanning the width of the continental shelf, with larger individuals shifting to reefs with increasing vertical height and complexity.…”
Section: Red Snapper Life-cycle and The Need To Scale Catch To Commonmentioning
confidence: 99%